The impact of green finance on profitability with credit risk as an intervening variable - Afifah Afifah; Erna Listiana; Wendy Wendy; Mustarudin Mustarudin; Giriati Giriati (International Journal of Applied Finance and Business Studies, 2023)
Sustainable Development Goals (SDGs) have become a global concern and have touched various industrial sectors. Through the application of green finance in the financial industry, green credit is provided by banks to support the sustainability of business projects based on environmental sustainability as determined in the Sustainability in the Sustainable Business Activity Category (KKUB) by OJK. On the other hand, as profit-oriented companies, banks need to consider how it impacts credit risk and banking profitability. Using credit risk as an intervening variable, this study seeks to establish the correlation between green finance and profitability of banks listed on the Indonesia Stock Exchange. This research uses the path analysis method and a quantitative study using the financial statements of banks that apply green finance for 2018-2022. The result shows that green lending (green finance) positively affects credit risk and negatively impacts bank profitability. Other result shows that credit risk can mediate the development of green lending on profitability.